ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK DALAM PEMIKIRAN RAJA ALI HAJI - Pery Rehendra Sucipta; Rilo Pambudi S (Jurnal Hukum Peratun, 2019)
This brief writing tried to challenge the old thinking that led everyone to the Raja Ali Haji figure as a literary and cultured man in the 19th century of the Malay Kingdom of Riau-Lingga. Whereas he was a multidisciplinary of science, who also included the politics, government, and constitutional law. His expertise on that subject was inseparably based on his experience as a kingdom adviser. As well as two books that specifically containing a law thought that are Muqaddimah fi Intizam and Tsamarat Al-Muhimmah. This study uses a normative juridical approach with the quality of research is analytic descriptive. The studies explain that: First, the legitimacy of Raja Ali Haji as a jurist, among other things: Gurindam Dua Belas is not a mere literacy work, it also includes the idea of contitutional law; the kingdom adviser; and review of his books. Second¸the general principles that are included in Muqaddima fi-Intizam and Tsamarat al-Muhimmah include the principle of consensus, the principle of prudence, the principle of juctice, the principle of unfairness, the principle of professionality, the principle of accountability, the principle of legality, the principle of public interest, and the principle of not mixing authority.